Investigation of Digital Signal Processing for Measurement of Dynamic Parameters of High-Speed DAC‘s - Kvedaras, R.; Kvedaras, V. (Elektronika ir Elektrotechnika, 2008)
Developed LabView Virtual Instrument (VI) for digital signal processing of sampling converter signal for measurement of serttling times of high-speed high resolution DACs is presented. Investigations performed by setting DAC output signal parameters set to noise level to 0.8 of readout levels (exceeding values of 12 bit resolutions DACs with 0.5 LSB readout levels) and also by setting noise level voltage to 4 LSB (exceeding noise level of real testers for 14 bit DACs). Investigations have shown that it is possible to achieve 3 % maximum inaccuracy by processing 15 realizations of 12 bit DAC signals and 500 realizations of 14 bit DAC signals. Ill. 3, bibl. 9 (in English; abstracts in Lithuanian, English, Russian).